2021
DOI: 10.21037/tlcr-20-754
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bisphosphonate and radiation therapy in bone-metastatic lung adenocarcinoma: the impact of KRAS mutation

Abstract: Background: KRAS mutation is the most common genetic alteration in lung adenocarcinoma (LADC) in Western countries and is associated with worse outcome in bone-metastatic cases. Yet, to date, no effective treatment guidelines were developed for these patients. Accordingly, our aim was to investigate the impact of KRAS mutation on bisphosphonate (BTx) and radiation therapy (RTx) in bone-metastatic LADC patients.Methods: Clinicopathological variables of 134 consecutive LADC patients with bone metastases at diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Of note, KRAS mutation was found to be a negative prognosticator in these patients. Therefore, KRAS mutational status should be considered when making decisions in bone metastatic LADC patient therapy ( 17 ). In addition, according to the “seed and soil” hypothesis, the histological subtype and the mutational status of the primary tumor might also have an impact on the specific metastasis patterns ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, KRAS mutation was found to be a negative prognosticator in these patients. Therefore, KRAS mutational status should be considered when making decisions in bone metastatic LADC patient therapy ( 17 ). In addition, according to the “seed and soil” hypothesis, the histological subtype and the mutational status of the primary tumor might also have an impact on the specific metastasis patterns ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…RTx is performed primarily for pain relief, control of a bone affected by metastases and prevention of pathologic fractures ( 15 , 16 ). Of note, oncogenic driver mutations should be taken into consideration during the administration of BTx and RTx since the beneficial effects of both therapeutic modalities might be less pronounced in patients with KRAS mutant tumors ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective analysis tested the efficacy of bevacizumab in combination with chemotherapy and demonstrated that it is more efficient in KRAS wild-type tumors which was due to the resistance of the G12D mutant form [ 15 ]. Analysis of the treatment outcome of bone metastatic lung carcinoma patients indicated that the KRAS mutant tumors seems to be resistant to radiation therapy and to bisphosphonates [ 16 ] as it was predicted by the preclinical models [ 17 ]. A recent analysis of the G12D mutant lung cancers demonstrated that the density of CD8 + T cells, the TMB and the tumor cell expression level of PDL1 are lower as compared to other KRAS mutants including G12C [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer‐related incidence and mortality, with non‐small‐cell lung cancer (NSCLC) as the most prevalent form with a poor 5 years survival of ~15% 1‐3 . Lung adenocarcinoma (LADC), characterized by high malignancy, short overall survival and loss of functional independence, is constituting the majority of newly diagnosed NSCLC cases and continuously rising in incidence 4‐6 . Unfortunately, the majority of patients already have advanced‐stage disease at diagnosis with different types of distant organ metastases 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Lung adenocarcinoma (LADC), characterized by high malignancy, short overall survival and loss of functional independence, is constituting the majority of newly diagnosed NSCLC cases and continuously rising in incidence 4‐6 . Unfortunately, the majority of patients already have advanced‐stage disease at diagnosis with different types of distant organ metastases 5 . In addition to surgery, LADC therapy includes radiation therapy, chemotherapy, molecule‐targeted therapy and cellular immunotherapy, which has been gradually maturing in recent years 1 .…”
Section: Introductionmentioning
confidence: 99%